Development of Foam Indicator Based on Cationic Surfactant Quaternized Fatty Acid Triethanolamine Ester - Krishna Mohan, S.; Srivastava, Tanu; Govindarajan, K.V. (Asian Journal of Chemistry, 2011)
Quaternized fatty acid triethanolamine esters have been found to be used predominantly for commercial applications in recent years for preparing foam indicators. They possess low toxicity, high biodegradability, excellent hydrolytic stability, antistatic, softening, corrosion inhibition properties and excellent dispersing properties. Quaternized fatty acid triethanolamine ester is produced via a two-stage process in which triethanolamine is first esterified with a fatty acid followed by quaternization with alkylating agent. Foam indicator has been formulated based on this and evaluated its leak rate up to 10-4 mbar/s.